Some Matrix Iterations for Computing Matrix Sign Function. (9th July 2014) - Soleymani, F.; Tohidi, E.; Shateyi, S.; Haghani, F. Khaksar
Abstract : Some iterative methods are introduced and demonstrated for finding the matrix sign function. It is analytically shown that the new schemes are asymptotically stable. Convergence analysis along with the error bounds of the main proposed method is established. Different numerical experiments are employed to compare the behavior of the new schemes with the existing matrix iterations of the same type.